2020
DOI: 10.1186/s13018-020-02005-w
|View full text |Cite
|
Sign up to set email alerts
|

One-stage posterior debridement and single-segment interbody fusion for treating mono-segmental lumbar and lumbosacral spinal tuberculosis in adults following minimum 5-year follow-up

Abstract: Background To evaluate the mid-long-term outcomes of surgical management of mono-segmental lumbar and lumbosacral spinal tuberculosis (TB) in adults by one-stage posterior debridement, single-segment fixation, and titanium mesh cage interbody fusion. Methods A total of 62 patients with mono-segmental lumbar or lumbosacral spinal tuberculosis were enrolled. One-stage posterior debridement, single-segment fixation, and titanium mesh cage interbody fusion was performed. Clinical and radiographic outcomes were c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…The surgical method for the treatment of TB in the lumbosacral junction is still controversial 20 , 21 , 22 . An anterior approach has been conventionally preferred since most TB lesions involve the vertebral body and intervertebral discs.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical method for the treatment of TB in the lumbosacral junction is still controversial 20 , 21 , 22 . An anterior approach has been conventionally preferred since most TB lesions involve the vertebral body and intervertebral discs.…”
Section: Discussionmentioning
confidence: 99%
“…However, surgery is required for patients with severe spinal deformity, vertebral instability, cold abscess formation, spinal cord nerve injury, and paraplegia. In such cases, surgery can be used to significantly improve its cure rate and reduce recurrence and related complications [ 4 , 5 ]. A typical surgery protocol includes removal of the spinal tuberculosis lesions followed by autologous bone defect repair and lastly, internal fixation to restore the biomechanical stability of the spine [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, no well-designed, prospective clinical trial has been performed for addressing this question. According to some retrospective studies on spinal TB surgical treatment, preoperative ATT duration times were applied arbitrarily, i.e., from 1 day to 3 months, and sometimes even longer [8][9][10]. The influence of preoperative ATT duration on the prognosis of bone TB is highly conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of preoperative ATT duration on the prognosis of bone TB is highly conflicting. Multiple studies found that preoperative ATT duration time did not cause differences in postoperative recurrence or non-healing of spinal TB [ 8 , 9 ], whereas Yang and Liu reported that inadequate preoperative ATT was an important risk factor of recurrence or non-healed spinal TB [ 10 ].…”
Section: Introductionmentioning
confidence: 99%